The Comments of Chinese "Zhihu" Netizens on the U.S. Sanctions Against Huawei: The Role of anti-Western Centrism in Nationalist Narratives - Yawei Chen; Abdul Mua’ti @Zamri Ahamd; Mastura Mahamed; Diyana Kasimon (Asian Journal for Public Opinion Research)
From 2018 to 2020, the United States has repeatedly imposed sanctions on the Chinese company Huawei, which has triggered strong nationalist sentiments on the Chinese Internet. This paper is a qualitative content analysis of Zhihu netizens' views on US sanctions against Huawei to explore how anti-Western centrism influences young people's narratives. The results showed that they believe the Huawei matter is a deliberate hegemonic act by the United States because it fears the decline of its own technological status. Moreover, it is direct evidence that the United States is deliberately destroying China's economic development environment to slow down China's rise, as well as a typical manifestation of the injustice of the liberal international order. A further analysis revealed that their narrative logic is obviously influenced by the following aspects: 1) The mentality of national glory derived from comprehensive national strength leads them to believe that U.S. sanctions against Huawei are an obstacle to China's rise. 2) National humiliation leads them to view U.S. sanctions as a constant insult to China. 3) China's superiority created by China's comprehensive national strength and its scientific and technological achievements in recent years has boosted its confidence to challenge the West's absolute progress. This study examines the impact of anti-Western centrism on Chinese nationalist sentiment and offers a bottom-level perspective on the debate over the crisis of the liberal order.